Number and distribution of Barnacle Goose Branta leucopsis colonies on the Timansky coast of the Barents Sea in 2009 - Dorofeev, Dmitry; Anisimov, Yury; Anisimova, Olga; Litvin, Konstantin (Ornis Norvegica, 2013)
During the summer of 2009 we conducted a survey of the coastal zone of the Barents Sea (approx. 330 km) between the Velt River and Peschanka-To Lake. The work was aimed at mapping Barnacle Goose Branta leucopsis colonies. We succeeded in describing 12 colonies, containing a total of 4650 Barnacle Goose nests. Some of these colonies are known since the middle of the 1990s, although most were described for the first time. We found the nests predominantly on the lower marshes or sandy islands. Using the inventory in combination with data from satellite images, we estimated the number of breeding pairs along the stretch of coast between Cape Kanin and the Velt river mouth. We suspected that there are not more than 800–1000 pairs of Barnacle Geese along this stretch of coast. This brings the estimate for the total number of breeding pairs from Cape Kanin to Russkiy Zavorot in 2009 to at about 5500–6000 pairs.